Análise de fatores ergonômicos em atividades de implantação florestal - Britto, Pedro Caldas de (2012)
The objective of this research was to conduct an assessment of ergonomic factors in implementing forest activities, aiding the decision making for improved comfort, health and safety of forest workers. The study was conducted in a forestry company located in the northern region and in the pioneering fields doss General, State of Parana, planting activities involving the manual, with application of gel, the fertilizer, herbicide application, mowing and semi mechanized. In research studies on the human factors and working conditions through interviews applied in the form of individual questionnaires to employees. It was established the anthropometric profile of the population over 41 measurements collected in 250 forestry workers deployment. Being the main anthropometric variables related to the tools used in each activity, proposing adjustments where necessary in accordance with the measures of the population in percentiles 5%, 50% and 95%. Was also carried out an assessment of discomfort with the use of a questionnaire with map of postural discomfort, also through interviews with workers, which allowed us to identify the frequency of occurrence and intensity of discomfort pain in different body regions for each activity . In addition, we performed a biomechanical evaluation using footage of workers in three percentiles, classified according to the stature of the population (5%, 50% and 95%) for each activity, and the data analyzed in the "software "3DSSPP Program (Prediction of Static Force Posture and 3D). The results show that the average age of workers was about 35 years, is 89.23% of rural origin, 52% are married and 77.53% are of low education (elementary school). As for length of service in the company, the average was 14.9 months and median time to experience in the position of 12.46 months. The stature of the workers is 156.8, 167 and 178.5 cm respectively representing percentiles 5%, 50% and 95%. The results of anthropometric evaluation showed a need for tools with different settings and adapted to variations of anthropometric workers, such as the dimensions of the feet, hands, arms reach away, standing height, among others. The questionnaires discomfort pain proved that the most problematic regions are the shoulders and legs, which can be justified due to the weight carried and because the distances traveled in areas of difficult access and with residue from timber harvesting. In biomechanical evaluations the hip and shoulder were the most affected, but with little risk of injury to workers. In the activities of planting and fertilizing, workers higher (95% percentile) had greater potential for injury than workers in the 5% percentile (lower workers), which can be justified due to improper posture adopted because of the dimensions the tools used.